Classificação multicritério de distritos de vendas de agronegócio - Oda, Rodrigo Denda [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Multi-criteria decision methods have provided numerous benefits for solving planning and management problems in several companies. The present work aims to develop a system of criteria and procedures to classify, by complexity, the sales districts of a multinational company of the agribusiness sector, in order to allocate to each district human resources with professional experience compatible with the necessities present there. The choice of the set of indicators that will allow to characterize the complexity in the management of the sales operations was made with the involvement of the managers. Classification was obtained through multi-criteria analysis using the AHP (Analytic Hierarchy Process) method. The main result obtained is a proposal containing the indicators and the index, all the procedures to measure them periodically and communicate the results, already tested, to be validated with the managers

Os métodos de decisão multicritério vêm proporcionando inúmeros benefícios para a resolução de problemas de planejamento e gerenciamento em diversas empresas. O presente trabalho tem como objetivo desenvolver um sistema de critérios e procedimentos para classificar, por complexidade, os distritos de vendas de uma empresa multinacional do setor do agronegócio, de forma a alocar a cada distrito recursos humanos com experiência profissional compatível com as necessidades ali presentes. A escolha do conjunto de indicadores que permitirá caracterizar a complexidade na gestão das operações de vendas foi feita com envolvimento dos gestores. A classificação foi obtida por meio da análise multicritério utilizando o método AHP. O principal resultado obtido é uma proposta contendo os indicadores e o índice, todos os procedimentos para mensurá-los periodicamente e comunicar os resultados, já testada, a ser validada com os gestores
Multicriteria classification of agribusiness sales districts
Keywords: Concreto armado; Patologia; Fibras de carbono; Reinforced concrete